La città del sole : dialogo poetico = The City of the Sun : a poetical dialogue - Campanella, Tommaso, 1568-1639.; Donno, Daniel John, 1920- (Berkeley : University of California Press, 1981)
Drummond -- Who I am -- Bummer summer -- After the baby -- Neighbors -- Drum and Dorene -- Meeting Dorene -- Race -- Tall tale -- New boy -- Drum, Dorene and Louis -- Someone -- Party -- Tall tale, too -- Going to get Rae -- Drum, Dorene, Louis and Rae -- Rae -- Promise -- Playground -- Friendly four -- Rain -- Fuss -- Punished -- When summer ends -- Let's make a town -- Here comes the truck -- We did it! -- In the town of Goodsummer -- Parade -- At the movies -- At the bank -- At school -- At the office building -- At the library -- At the pet shop -- At the concert hall -- Goodbyes -- Goodbye, Rae -- E-mail -- Goodbye to Goodsummer.
Drum: Didn't I call this summer a bummer? All: Not anymore, not anymore. Drum: I was alone, and life was lonely. All: But not anymore, Drum: 'cause we're the Friendly Four! Louis, Dorene, Rae: The Friendly Four? Drum: The Friendly Four. Meet Drum, Dorene, Louis, and Rae as they share one special summer of discovery and creative play together. Through individual poems and poems for multiple voices, these four young people explore the bonds of friendship, family, and community. With her free-verse poetry, award-winning writer Eloise Greenfield poignantly reminds us that sometimes our truest friends enter our lives when we least expect them. With inspired illustrations by renowned artist Jan Spivey Gilchrist.
Translation of Civitas Solis.
Translation based on the Italian text edited by Luigi Firpo.
Text in English and Italian; introd. and notes in English.
Includes bibliographical references (pages 143-144).
Text in English and Italian, introduction and notes in English.
JSTOR
Keywords: Utopias -- Early works to 1800.; Utopias; Utopias; Utopies; Utopies -- Ouvrages avant 1800.; Utopias; Utopieën.; Italiaans; Utopias; Utopian fiction; Early works; Utopian fiction; Utopian fiction